+0  
 
0
45
1
avatar+560 

Let $f(x) = 3x-8$ and $g(f(x)) = 2x^2 + 5x - 3.$ Find $g(-5).$

Lightning  Jul 15, 2018
 #1
avatar
+1

g(-5) equals g(f(x) so f(x) must equal -5. So

 

3x - 8 = -5.

 

Solving this gives x = 1. So now g(-5) equals

 

2 * 25 - 25 - 3 = 22. 

Guest Jul 15, 2018

17 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.